A novel “hitch-and-ride” deep biliary cannulation method during rendezvous endoscopic ultrasound-guided ERCP technique - Nakai, Yousuke; Isayama, Hiroyuki; Matsubara, Saburo; Kogure, Hirofumi; Mizuno, Suguru; Hamada, Tsuyoshi; Takahara, Naminatsu; Nakamura, Tomoka; Sato, Tatsuya; Takeda, Tsuyoshi; Hakuta, Ryunosuke; Ishigaki, Kazunaga; Saito, Kei; Tada, Minoru; Koike, Kazuhiko (Endoscopy, 2017)
Background and study aim Endoscopic ultrasound-guided rendezvous (EUS-RV) is increasingly reported as a treatment option after failed endoscopic retrograde cholangiopancreatography. We developed a novel “hitch-and-ride” catheter for biliary cannulation to reduce the risk of guidewire loss during EUS-RV.Patients and methods We retrospectively evaluated safety and technical success of EUS-RV between June 2011 and May 2016. Biliary cannulation during EUS-RV using three methods – over-the-wire, along-the-wire, and hitch-and-ride – were compared.Results A total of 30 EUS-RVs were attempted and the technical success rate was 93.3 %, with two failures (one bile duct puncture and one guidewire insertion). After 28 cases of successful guidewire passage, cannulation was attempted by the over-the-wire (n = 13), along-the-wire (n = 4) or hitch-and-ride (n = 11) method. Only the hitch-and-ride method achieved biliary cannulation without guidewire loss or conversion to the other methods. Time to cannulation was shorter with the hitch-and-ride method (4 minutes) than with over-the-wire and along-the-wire methods (9 and 13 minutes, respectively). The adverse event rate of EUS-RV was 23.3 %.Conclusion A novel hitch-and-ride catheter was feasible for biliary cannulation after EUS-RV.